Redox-mediated transformation of a Tb2O3(111) thin film from the cubic fluorite to bixbyite structure. Issue 1 (10th December 2019) - Lee, Christopher J.; Sayal, Ameen; Vashishtha, Saumye; Weaver, Jason F.
Abstract : Repeated oxidation and reduction transforms a cubic fluorite Tb2 O3 (111) film to the bixbyite structure. Abstract : We used temperature programmed desorption (TPD) and low energy electron diffraction (LEED) to investigate the isomeric structural transformation of a Tb2 O3 thin film grown on Pt(111). We find that repeated oxidation and thermal reduction to 1000 K transforms an oxygen-deficient, cubic fluorite (CF) Tb2 O3 (111) thin film to the well-defined bixbyite, or c-Tb2 O3 (111) structure, whereas annealing the CF-Tb2 O3 (111) film in UHV is ineffective in causing this structural transformation. We estimate that the final stabilized film consists of about ten layers of c-Tb2 O3 (111) in the surface region plus about eight layers of CF-Tb2 O3 (111) located between the c-Tb2 O3 (111) and the Pt(111) substrate. Our measurements reveal the development of two distinct O2 TPD peaks during the CF to bixbyite transformation that arise from oxidation of c-Tb2 O3 domains to the stoichiometrically-invariant ι-Tb7 O12 and δ-Tb11 O20 phases and demonstrate that the c-Tb2 O3 phase oxidizes more facilely than CF-Tb2 O3 . We present evidence that nucleation and growth of c-Tb2 O3 domains occurs at the buried TbO x /CF-Tb2 O3 interface, and that conversion of the interfacial CF-Tb2 O3 to bixbyite takes place mainly during thermal reduction of TbO x above ∼900 K and causes newly-formed c-Tb2 O3 to advance deeper into the film. The avoidance of low Tb oxidation states may facilitate the CF to bixbyite transformation via this redox mechanism.